2014
DOI: 10.1021/am5009437
|View full text |Cite
|
Sign up to set email alerts
|

Protein Induced Aggregation of Conjugated Polyelectrolytes Probed with Fluorescence Correlation Spectroscopy: Application to Protein Identification

Abstract: The interaction of a series of water-soluble conjugated polyelectrolytes with varying backbone structure, charge type (cationic and anionic), and charge density with a set of seven different proteins is explored by using fluorescence correlation spectroscopy (FCS). The FCS method affords the diffusion time for a particular CPE/protein pair, and this diffusion time is a reflection of the aggregation state of the polymer/protein in the solution. The diffusion time is larger for oppositely charged CPE/protein com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…Adding fluorophores to samples proved to be an efficient way of improving the discrimination performance using fluorescent fingerprinting when the samples are not intensely fluorescent or are not well discriminated by their intrinsic fluorescence [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The discrimination performance should be quantitatively characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding fluorophores to samples proved to be an efficient way of improving the discrimination performance using fluorescent fingerprinting when the samples are not intensely fluorescent or are not well discriminated by their intrinsic fluorescence [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The discrimination performance should be quantitatively characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Most fluorimetric fingerprinting classification methods use intrinsic fluorescence of samples [ 1 , 2 ]. A less developed approach is based on adding fluorophores to samples [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], which promises their better discrimination because of the interaction of fluorophore(s) with non-fluorescent components of the sample and corresponding changes in the spectrum. If more than one fluorophore is added to samples, we can talk about fluorescent sensor arrays [ 4 , 5 , 8 , 10 , 11 , 15 , 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] Several efforts have been made to understand the aggregation behavior of surfactants, polymers, proteins and ionic liquids in aqueous and non-aqueous media using FCS as a potential alternative technique. [38][39][40][41] It has recently been demonstrated that FCS can be used as an efficient tool to determine the size, size distribution and polydispersity of various surfactant assemblies. [42][43][44][45][46][47][48] In this work, we have investigated the diffusion properties of different self-assemblies of oleic acid/ [C 16 mim]Cl system such as micelles, large unilamellar vesicles and vesicles with varying pH using FCS technique.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This improved solubility makes them highly desirable as optical sensors for a range of biological systems, 3,4 with the ionic terminal groups additionally serving as analyte recognition sites. 5,6 This approach has been elegantly demonstrated for various large bioanalytes such as DNA, 7,8 proteins, 9 lipids 10 and enzymes. 11 Ionic polythiophenes have been developed for a wide range of biosensing platforms due to their excellent optical properties and the possibility for self-assembly.…”
Section: Introductionmentioning
confidence: 99%